2011
DOI: 10.1159/000327915
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Homogeneous Subgroups Reveals Association between <i>PDE4D</i> Gene Variants and Ischemic Stroke

Abstract: Background: An Icelandic study showed a significant positive association between phosphodiesterase 4D (PDE4D) gene variants and stroke. However, subsequent studies reported conflicting results, possibly due to small sample sizes and the heterogeneity of the studies. Method: We performed a meta-analysis on 6 SNPs of the PDE4D gene to investigate the association between this gene and ischemic stroke by integrating the results of previous studies, comprising 11,834 cases and 15,233 controls. A pooled genotypic od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 86 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…A previously published meta-analysis, with similarities to ours regarding selection of publication, presented a significant overall OR¼1.29 (P¼0.05) after removal of publications causing heterogeneity. 27 The slightly significant heterogeneity test (P¼0.042) suggests a nonrandom effect explaining the difference between the ORs among the 20 compared populations in our meta-analysis. Figure 1 visualises this ambiguity regarding the OR estimates.…”
Section: Meta-analysis Findingsmentioning
confidence: 76%
“…A previously published meta-analysis, with similarities to ours regarding selection of publication, presented a significant overall OR¼1.29 (P¼0.05) after removal of publications causing heterogeneity. 27 The slightly significant heterogeneity test (P¼0.042) suggests a nonrandom effect explaining the difference between the ORs among the 20 compared populations in our meta-analysis. Figure 1 visualises this ambiguity regarding the OR estimates.…”
Section: Meta-analysis Findingsmentioning
confidence: 76%
“…However, other studies failed to establish an association Kuhlenbaumer et al, 2006;Matsushita et al, 2009;Staton et al, 2006;Sun et al, 2009). A recent meta-analysis by Yoon et al found the most significant association of SNP56 with ischemic stroke (Yoon et al, 2011). They integrated the results of previous studies, comprising 11,834 cases and 15,233 controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cohorts of different ethnicities have been studied. A detailed account of all these follow-up studies has already been reviewed Yoon et al, 2011). Inflammation has emerged as a key factor in the development of atherosclerotic lesions and in the progression to mature atheroma (Quarta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations